التقييم السريري للتغيرات اللعابية والمظاهر الفموية واللثوية لدى مرضى التحال الدموي - أمون, عمار; يوسف, محمد; سليمان, حسين (Latakia University Journal -Medical Sciences Series, 2019)
Background: Salivary changes in hemodialysis patients may result in various oral manifestations. This research intended to determine some oral manifestations and some salivary markers in hemodialysis patients. Material and Methods: This clinical study was conducted on 35 hemodialysis patients (the patient group) and 35 healthy individuals (the control group). Saliva urea, OHI-s, salivary volume and pH values of the participants were measured. The data was analyzed using T-test and chi-square, and p<0.05 was considered to be significant. Results: The mean salivary urea level, OHI-s and pH value in the patient group were significantly higher compared to those of the control group (p<0.05), but salivary volume were significantly lower in the patient group compared to those of the control group (p<0.05). Conclusions: Advanced chronic renal insufficiency can increase salivary urea level, pH value, OHI-s and decrease salivary volume. تُسبّب التغيرات اللعابية لدى مرضى التحال الدموي العديد من التظاهرات الفموية. يهدف البحث لتحديد بعض المظاهر الفموية والتغيرات اللعابية لدى مرضى التحال الدموي. شملت الدراسة 35 مريضاً مصاباً بالفشل الكلوي يجرون التحال الدموي (صفات الدراسة)، و35 شخصاً سليماً (المجموعة الشاهدة). تمّ تحرّي قيم PH اللعاب وتركيز البولة في اللعاب وحجم اللعاب ومشعر الصحة الفموية المبسط, وتمّ تحليل النتائج باستخدام اختبار مان وتني وكاي مربع كون البيانات لا تخضع للتوزيع الطبيعي. أظهرت النتائج أنّ تركيز البولة في اللعاب وقيمة PH اللعاب ومشعر الصحة الفموية المبسط كان أعلى لدى مرضى التحال الدموي مقارنة بالمجموعة الشاهدة (P<0.05), في حين كان حجم اللعاب أقل لدى هؤلاء المرضى مقارنة بالمجموعة الشاهدة (P<0.05). يزداد تركيز البولة في اللعاب وقيمة PH اللعاب ومشعر الصحة الفموية المبسط لدى مرضى التحال الدموي المتقدم في حين يتناقص حجم اللعاب لديهم.